EFFECT OF SALICYLIC ACID IN SOYBEAN (GLYCINE MAX L. MERIL) UNDER SALINITY STRESS - JAISWAL, AKANKSHA; V. PANDURANGAM; S. K. SHARMA (The Bioscan, 2014)
The present investigation was carried out to elucidate the mechanism of salinity tolerance by exogenous supply of salicylic acid at two concentrations viz. 100 and 200 ppm under created salinity stress of 50 mM and 100 mM NaCl in the soil. To check the efficacy of salicylic acid under salinity at 45, 60 and 75 days after sowing, foliar spray was done to study on biochemical parameters which lead to significant increase in chlorophyll content as well as sugar and starch content at the level of 100 ppm salicylic acid. Proline, one of the stress induced amino acid at concentration of 200 ppm also showed increased level indicating its potential role in combating salinity stress. Similar results were obtained for antioxidative enzymes like SOD and CAT at the level of salicylic acid at 200 ppm.Thus, it can be concluded that application of salicylic acid at varying concentrations of 100 and 200 ppm can lead to overcome salinity situations upto a certain extent.